Taxation and unemployment: an applied general equilibrium approach for Germany - Stefan Boeters; Christoph Böhringer; Michael Feil (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper presents an applied general equilibrium model for Germany. The model integrates specific labour market institutions in an otherwise standard general equilibrium framework. There are sectoral wage negotiations for two skill types of workers between firms and trade unions. The bargaining setup is sensitive to the specific conditions of the respective sector (profits, output and labour demand elasticities, bargaining power) and generates wages that reflect empirical wage differentials across sectors. The model is used to simulate the labour market effects of changes in the taxation of labour: marginal and average wage tax, and social security contributions.
Keywords: D58; E62; J60; 330; applied general equilibrium; Germany; labour market; trade unions; wage bargaining; tax policy; tax progression; labour mobility; Steuerpolitik; Lohnsteuer; Sozialversicherungsbeitrag; Steuerwirkung; Beschäftigungseffekt; Allgemeines Gleichgewicht; Lohnverhandlungstheorie; Lohnstruktur; Arbeitsmobilität; Arbeitslosigkeit; Theorie; Deutschland